2020
DOI: 10.1097/ajp.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

What Works? Processes of Change in a Transdiagnostic Exposure Treatment for Patients With Chronic Pain and Emotional Problems

Abstract: Objectives:We recently developed a transdiagnostic exposure treatment ("the hybrid treatment") for chronic pain patients with concurrent emotional difficulties. This paper investigates the hypothesized treatment processes, specifically: a) if changes on pain-related dysregulation (catastrophizing, fear-avoidance and non-acceptance of pain) and general emotion dysregulation (difficulties to regulate a broad spectrum of emotional responses) mediate effects on outcomes; and b) if mediation is more pronounced for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Leeuw et al (2008) showed that pain-related fear and catastrophizing mediated the effects of exposure in vivo on disability compared to graded activity, accounting for 75% of the total effect. Sodermark et al (2020) reported that a latent variable consisted of pain-related fear, catastrophizing and acceptance mediated the effects of a hybrid CBT intervention (including techniques addressing comorbid depression) on disability compared to traditional CBT. Lastly, Wetherell et al (2011) compared the mediated effects of pain acceptance and self-efficacy on disability between CBT and ACT and reported no mediated effects for any of them.…”
Section: Results Of the Narrative Synthesis: Mediated Effects Between...mentioning
confidence: 99%
See 2 more Smart Citations
“…Leeuw et al (2008) showed that pain-related fear and catastrophizing mediated the effects of exposure in vivo on disability compared to graded activity, accounting for 75% of the total effect. Sodermark et al (2020) reported that a latent variable consisted of pain-related fear, catastrophizing and acceptance mediated the effects of a hybrid CBT intervention (including techniques addressing comorbid depression) on disability compared to traditional CBT. Lastly, Wetherell et al (2011) compared the mediated effects of pain acceptance and self-efficacy on disability between CBT and ACT and reported no mediated effects for any of them.…”
Section: Results Of the Narrative Synthesis: Mediated Effects Between...mentioning
confidence: 99%
“…After the first screening of titles and abstracts, 152 publications were retrieved for full-text screening. Finally, 37 studies were included with a total of 28 mediation analyses (n = 4652) (Cederberg, Cernvall, Dahl, von Essen, & Ljungman, 2016;Chalder, Goldsmith, White, Sharpe, & Pickles, 2015;Coronado et al, 2020;Durá-Ferrandis, Ferrando-García, Galdón-Garrido, & Andreu-Vaillo, 2017;Fordham, Ji, Hansen, Lall, & Lamb, 2017;Garland et al, 2019;Hedman-Lagerlof et al, 2019;Leeuw et al, 2008;Lin, Klatt, McCracken, & Baumeister, 2018;Luciano et al, 2014;Mansell, Hill, Main, Von Korff, & Van Der Windt, 2017;Mansell, Hill, Main, Vowles, & van der Windt, 2016;Mansell, Storheim, Løchting, Werner, & Grotle, 2017;Molinari et al, 2019;O'Neill, O'Sullivan, O'Sullivan, Purtill, & O'Keeffe, 2020;Pérez-Aranda et al, 2019;Simister et al, 2018;Smeets, Vlaeyen, Kester, & Knottnerus, 2006;Sodermark et al, 2020;Spinhoven et al, 2004;Taylor et al, 2018;Trompetter, Bohlmeijer, Fox, & Schreurs, 2015;Turner, Holtzman, & Mancl, 2007;van Koulil et al, 2011;Wetherell et al, 2011;Wiborg, Knoop, Frank, & Bleijenberg, 2012;Wicksell et al, 2013;Wicksell, Olsson, & Hayes, 2010) and 11 moderation analyses (n = 1925) (Broderick et al, 2016;Buckelew et al, 1996;Day et al, 2019;Flink, Boersma, & Linton, 2010;Lawford et al, 2018;...…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrative perspective of the three methods together might offer even more methodological potential. The far-reaching AA expertise concerning the technical implementation and practicalities of diverse sampling schemes (including multimodal assessments of passive data) could serve as a basis for improving other methodological approaches (e.g., Myin-Germeys et al, 2018; Södermark et al, 2020; Wichers et al, 2019). The NA approach makes a further contribution by revealing mutually reinforcing dynamics of the critical variables assessed (Fried & Cramer, 2017).…”
Section: Discussionmentioning
confidence: 99%